THE INEFFECTIVENESS OF EU’S COMMON EUROPEAN ASYLUM SYSTEM (CEAS) IMPLEMENTATION IN ADDRESSING ASYLUM SEEKERS PROBLEMS IN EUROPE 2015-2021 - Ana Maftuha (Mediasi: Journal of International Relations, 2022)
This study analyzes the extent of the effectiveness of the implementation of the Common European AsylumSystem (CEAS) as an asylum policy that the European Union applies to its member states. The EuropeanUnion, as an international institution, adopted the policy of the 1951 Geneva Convention contained in theCEAS. CEAS did not arise out of thin air but rather developed on the basis of political decisions taken bysupranational institutions and member states responsible for its implementation. In its implementation,CEAS is considered to be less effective due to different standards and concerns in each EU member state.The research objective in this study is to analyze the effectiveness of CEAS implementation in addressingasylum issues in Europe. The international regime is the analytical tool used by the authors in this study.The method used in this study is a qualitative method. According to the findings of this study, CEAS is stillineffective. The ineffectiveness of CEAS is caused by the large indications of problem malignancy factorscompared to problem solving capacity in CEAS, which can be an impediment in dealing with asylum issuesin Europe.Keywords: CEAS, European Union, Asylum Seeker, International Regime